Effect of Manual Traction on Cervical Myofascial Pain - M. Mudatsir Syatibi; Noerdjanah (Journal of Health and Therapy, 2022)
Cervical pain is widely in the community. The incidence rate of cervical pain is the second largest after low back pain. One of the most widely used therapeutic techniques for cervical pain is manual traction. Objective: to determine the effect of manual traction on cervical myofascial pain. This research was desained One group pre and post test design. Subject: physiotherapy students semester V and semester I Transfer Class Class Bachelor applied physiotherapy year 2021-2022 that meets the criteria of inclusion and exclusion, amounting to 12 people. Treatment: The treatment in this study was manual traction. Place and time of research: the research was conducted in the department of physiotherapy Poltekkes Surakarta in September 2021. Measuring instrument: Numerical Fating Scale (NRS). The Paired Sample T Test between before and after treatment, obtained a value of p = 0.000 (p<0.05) means that there is a very significant influence of manual traction can reduce cervical myophyasial pain. Conclusion: Manual traction can decrease cervical myofascial pain.